Saying ‘No’ to Foreign Direct Investment in Wind Power Generation Sector by Attracting Indigenous Entrepreneurs: A Step towards Self-reliance - Qureshi, Jawaid Ahmed; Waqas, Muhammad Waqas; Qureshi, Shahid (International Journal of Economics and Financial Issues, 2018)
Pakistan opened its gates for foreign direct investment (FDI) in 1970s. The power sector was regulated by government itself. Considering public sector limitations and energy shortfall, later in 1994, Pakistan allowed independent power producers (IPPs) to install private power projects by providing them one-window operations through Private Power Infrastructure Board (PPIB). After realizing alternative renewable energy resources (wind, solar, biogas, and small hydel projects up to 50 megawatt), Pakistan established Alternative Energy Development Board (AEDB) with plan to install projects with alternative renewable energy (ARE) technologies by 2030 to produce up to 5% of total national power generation capacity. Pakistan has provided various incentives to attract investors including FDI. This qualitative inductive study focuses on to identify the indigenous potential of entrepreneurs and adopting a policy of self-reliance in wind power sector to avoid dependency on FDI. The sample is drawn from wind power projects/companies for conducting semi-structured interviews with open-ended questions. The participants’ views were converted into five broad themes. It was found that establishing wind power project is easy to install and it necessarily not relies on FDI, but rather policy framework is required to attract indigenous entrepreneurs, which will ultimately lead to self-reliance and overall sustainable socio-economic development. Keywords: Foreign Direct Investment; Wind Power/Alternative Renewable Energy; Entrepreneurship; Self-reliance JEL Classifications: F21, L26, Q2